Factors Influencing Informal Sector Workers’ Contribution to Pension Scheme in the Tamale Metropolis of Ghana - Adzawla, William; Baanni, Shaibu Azumah; Wontumi, Roger Fianko (Journal of Asian Business Strategy, 2015)
Social protection is an essential mechanism for a sustained poverty eradication and development. One of these social protection instruments is the informal pension scheme. In this study, the objective was to identify the factors that influenced informal sector workers’ decision into pension scheme as well as their contribution levels. Heckman two-stage approach was adopted in analyzing the data collected from 150 informal sector workers in the Tamale metropolis. It was revealed that the elderly, the single, the highly educated, highly depended and higher income workers have a higher probability of contributing to the informal pension scheme. Similarly, traders, artisans, highly educated and highly depended upon workers contribute higher amounts monthly. Although informal sector workers in general should be encouraged to remain loyal or join pension schemes, farmers in particular need to be re-targeted. In order to restore confidence in the pension scheme and ensure its sustenance, public education must be intensified.